Anaerobic co-digestion of leachate and glycerol for renewable energy generation. Issue 8 (3rd April 2022) - Takeda, Paula Yumi; Gotardo, Jackeline Tatiane; Gomes, Simone Damasceno
ABSTRACT: Anaerobic digestion is a versatile biotechnology that produces bioenergy, biogas, from wastewater. Biogas production and wastewater treatment can be optimized by associating substrates with complementary characteristics. In this context, the aim of this study was to evaluate the performance of the anaerobic co-digestion of different contents of landfill leachate and crude glycerol compared to the organic matter removal and specific biogas production, the effects of the factors (time, glycerol content and substrate/inoculum ratio) and their interactions on kinetic parameters of specific biogas production using the modified Gompertz model. A Central Composite Rotational Design (CCRD) was performed for the experimental variables: time (16.6, 20, 25, 30 and 33.4 days), glycerol content (0.43, 0.70, 1.10, 1.50 and 1.77%) and substrate/inoculum ratio (0.23, 0.30, 0.40, 0.50 and 0.57 g COD/g VSS). From the optimization, it was possible to maximize the efficiency of organic matter removal (90.15%) and specific biogas production (403.15 mL/g VSS) in the conditions of 33.2 days, glycerol content of 1.71% and substrate/inoculum ratio of 0.37 g COD/g VSS. Concerning the modified Gompertz model of the optimal condition performed, an average of 20.3 times higher specific biogas production was obtained when compared to the monodigestion of leachate. Therefore, the association of leachate and glycerol was found to be feasible in terms of stability, biodegradability and biogas production. GRAPHICAL ABSTRACT: UF0001